Methodology for Results-Based Accountability within the Public Sector - Lerner, Emilia Raquel (Revista del CLAD Reforma y Democracia, 2021)
This paper aims to develop a methodology for results-based accountability in public organizations, defining guidelines that support the advance of an accountability process in these organizations. A conceptual framework merging the principles of results-based accountability and the relevant criteria and instruments for its effective development is formulated. The proposal is based on a model that comprises five dimensions focused from the institutional point of view as well as the one of the individuals who are part of the organizations. To validate the methodology, an indicator has been proposed to estimate the level of development of the variables identified in each dimension of the methodology for each country selected in the sample. The proposed methodology was applied to the analysis of eight Latin American countries and two countries in North America. The results show that the highest values of the indicator are verified in those countries that give a higher priority to results-based evaluation, strategic planning, and national development plans in evaluation systems. The main findings indicate that not all Latin American countries have defined results-oriented budgeting and that, when it is defined, the experience is recent. There are also limitations related to the availability and use of information, the integration of systems and inter-institutional coordination, the weakness of the evaluation, self-evaluation and incentives mechanisms, the accountability mechanisms, and the lack of instruments for citizen consultation and social responsability. Given the fact that there is no univocal consensus on the nature of the idea o accountability and its scope, and that there are several ways of using the term, even contradictory ones, the main contribution of this paper for disciplinary development is that it proposes to specify the scope and tools of result-based accountability, wich enabels to delimit its meaning in the institutional framework of each country.